An improvement to the performance measurement system of the logistics operation - Jamaludin, Khairur Rijal (The Institution of Engineers Malaysia, 2007)
Logistics and supply chain management has become common practices across all industries. However, the topic of Logistics Performance Measurement does not receive adequate attention therein. A good performance measurement system is a necessity for a company to grow and sustain industry leadership. The paper presents the research report studied at one of the largest gas manufacturer in Malaysia. The study is to understand the existing logistics operation performance measurement system practiced in the company in terms of delivery service, delivery reliability, delivery service measurement, safety aspects, productivity management and, distribution cost management. Beside that, the study will also identify the drawbacks and suggests improvements in line with the world class practices. The scope of the study is focusing on analysing the current practice performance measurement system which related with safety, productivity, costs and delivery reliability. Management analysis tools such as Competitive Profile Matrix, Gap analysis, SWOT analysis, Pareto analysis and Key Performance Indicators have been used in the study. These tools are used as a foundation for developing the overall performance measurement system that measures every department's performance